Evolution : the adaptation and survival of species - Lew, Kristi. 4 0 16; 5 (New York : Rosen Publishing, 2011)
An introduction to evolution that explores the history of evolutionary theory, the evolution of populations, archaeological and genetic evidence for evolution, and other related topics.
Includes bibliographical references (p. 73-76) and index.
7.9;Young Adult;Young Adult.
Keywords: 2 -- 0; 6; Evolution (Biology) -- 20 -- Juvenile literature; 20; 2